Analysis of Earnings From the Master’s Educational Programs of Lesya Ukrainka Eastern European National University Using the ABC Method (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article analyzes revenues from 70 master’s educational programs of Lesya Ukrainka Eastern European National University by means of the ABC method, which allows to divide all analyzed objects into three groups depending on their specific weight in the aggregate size of the indicator: A (approximately 80 %), B (about 15 %), C (about 5 %). The article is a logical continuation of the previous study of the author on the income from the bachelor’s educational programs of this university. The table with quantitative and financial indicators that characterize all master’s programs of higher education institution is compiled. Groups A, B, C of the educational programs of Lesya Ukrainka Eastern European National University by the indicator of revenues from tuition fees of undergraduate students of the first year are determined. The university faculty ranking is based on the results of the ABC-analysis. The study was conducted on the basis of indicators for 2017. Group A received 21 master’s programs (30 %), which accounted 80 % of the total revenue from enrolled students in the first year of full-time study. To group B 13 (18,57 %) of educational programs were assigned, their contribution to the total income was 14 %. Group C combines 36 (51,43 %) educational programs, with a share of total revenue 6 %. In Lesya Ukrainka Eastern European National University 30 % of educational programs bring 80 % of the income from the training of masters who are studying in the first year of full-time education. The proportion was 30/80. The most popular were the following faculties: pedagogical; legal; information systems, physics and mathematics; geographical. The possible causes and possible ways to overcome the low profitability of masters’ educational programs are indicated.
Keywords: ABC-analysis, Lesya Ukrainka Eastern European National University, magister, educational program, tuition fee, faculty, rating.